Another alien on the horizon? First European record of Tautoneura polymitusa, an East Asian leafhopper (Hemiptera: Auchenorryncha: Cicadellidae) - Tóth, Mária; Orosz, András; Rédei, Dávid (Zootaxa, 2017)
The leafhopper species Tautoneura polymitusa Oh & Jung, 2016 (Hemiptera: Auchenorrhyncha: Cicadellidae: Typhlocybinae: Erythroneurini), described recently from Korea, is recorded from Hungary, representing the first known European occurrence of the species and also of the genus Tautoneura Anufriev, 1969. The species is illustrated, its diagnostic characters are discussed and compared with those of the closely related congeners. The occurrence of T. polymitusa in three isolated localities in Hungary and regular records in Budapest over a period of five years since 2012 indicate that stable populations exist in Hungary, the species is probably already established and it is locally abundant. It is apparently associated with elm trees (Ulmus spp.) and other members of the plant family Ulmaceae. Its further spread in Europe is expected.